Alternating block copolymer-based nanoparticles as tools to modulate the loading of multiple chemotherapeutics and imaging probes. (15th October 2018) - Mattu, C.; Brachi, G.; Menichetti, L.; Flori, A.; Armanetti, P.; Ranzato, E.; Martinotti, S.; Nizzero, S.; Ferrari, M.; Ciardelli, G.
Graphical abstract: Abstract: Cancer therapy often relies on the combined action of different molecules to overcome drug resistance and enhance patient outcome. Combined strategies relying on molecules with different pharmacokinetics often fail due to the lack of concomitant tumor accumulation and, thus, to the loss of synergistic effect. Due to their ability to enhance treatment efficiency, improve drug pharmacokinetics, and reduce adverse effects, polymer nanoparticles (PNPs) have been widely investigated as co-delivery vehicles for cancer therapies. However, co-encapsulation of different drugs and probes in PNPs requires a flexible polymer platform and a tailored particle design, in which both the bulk and surface properties of the carriers are carefully controlled. In this work, we propose a core-shell PNP design based on a polyurethane (PUR) core and a phospholipid external surface. The modulation of the hydrophilic/hydrophobic balance of the PUR core enhanced the encapsulation of two chemotherapeutics with dramatically different water solubility (Doxorubicin hydrochloride, DOXO and Docetaxel, DCTXL) and of Iron Oxide Nanoparticles for MRI imaging. The outer shell remained unchanged among the platforms, resulting in un-modified cellular uptake and in vivo biodistribution. We demonstrate that the choice of PUR core allowed a high entrapment efficiency of all drugs, superior or comparable to previously reported results, and that higher core hydrophilicity enhances the loading efficiency of the hydrophilic DOXO and the MRI contrast effect. Moreover, we show that changing the PUR core did not alter the surface properties of the carriers, since all particles showed a similar behavior in terms of cell internalization and in vivo biodistribution. We also show that PUR PNPs have high passive tumor accumulation and that they can efficient co-deliver the two drugs to the tumor, reaching an 11-fold higher DOXO/DCTXL ratio in tumor as compared to free drugs. Statement of Significance: Exploiting the synergistic action of multiple chemotherapeutics is a promising strategy to improve the outcome of cancer patients, as different agents can simultaneously engage different features of tumor cells and/or their microenvironment. Unfortunately, the choice is limited to drugs with similar pharmacokinetics that can concomitantly accumulate in tumors. To expand the spectrum of agents that can be delivered in combination, we propose a multi-compartmental core-shell nanoparticles approach, in which the core is made of biomaterials with high affinity for drugs of different physical properties. We successfully co-encapsulated Doxorubicin Hydrochloride, Docetaxel, and contrast agents and achieved a significantly higher concomitant accumulation in tumor versus free drugs, demonstrating that nanoparticles can improve synergistic cancer chemotherapy.